1993
DOI: 10.1159/000238979
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Evaluation of Imipenem Combined with Cilastatin in Cystic Fibrosis

Abstract: The pharmacokinetics of imipenem (MK-787) and cilastatin (MK-791) were studied in 30 patients with cystic fibrosis (CF) receiving the drug for therapeutic purposes at doses of 11 mg/kg given as a 30-min infusion. The serum concentrations and urine elimination were studied after the first dose and during steady state. The concentrations were assayed by high-pressure liquid chromatography. The total areas under the imipenem serum concentration curves (AUCs) to infinity were 30.4 ± 6.8 mg-h/1 after the first dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This is not surprising since studies with another carbapenem, imipenem, also resulted in similar pharmacokinetics when compared with a control group [5,8]. In a previous study, CF subjects had significantly greater clearance when compared to non-CF subjects, but this could have been the result of comparing children versus older adults [14].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is not surprising since studies with another carbapenem, imipenem, also resulted in similar pharmacokinetics when compared with a control group [5,8]. In a previous study, CF subjects had significantly greater clearance when compared to non-CF subjects, but this could have been the result of comparing children versus older adults [14].…”
Section: Discussionmentioning
confidence: 86%
“…The effect of CF on the pharmacokinetics of ß-lactam (semisynthetic penicillins, cephalosporin and carbapenem) antibiotics is Bui/Ambrose/Nicolau/Lapin/ Nightingale/Quintiliani variable [5][6][7][8][9][10][11], however, it most often results in more rapid elimination of these agents. These alterations may reduce the probability of clinical success by lowering the plasma concentrations and by shortening the duration of serum concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Four PK studies analyzing imipenem–cilastatin in 77 CF patients (age range 8–33 years) have been performed utilizing doses ranging from 45–100 mg/kg/day divided every 6 hr 45–48. The study by Reed et al45 concluded that imipenem–cilastatin administered at a dose of 90–100 mg/kg/day divided every 6 hr would be adequate to maintain serum imipenem concentrations above the MIC of the majority of P. aeruginosa isolates: S: ≤4 mg/L; R: >8 mg/L (EUCAST); S: ≤4 mg/L; R: >16 mg/L (CLSI; Tables 1 and 4).…”
Section: Introductionmentioning
confidence: 99%